Analysis of Production Process in Small Business Using Value Stream Mapping Approach - Anita Susilawati; Muhammed Sarwar; Toni Darji; Nur Iksan Agusti (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
This paper aims to identify waste and analyse production process activities using the Value Stream Mapping (VSM) in a small business as a case study. The waste was identified by a waste relationship matrix and waste assessment questionnaire to determine the percentage of waste that occurs. Furthermore, a detailed selection of waste mapping based on the value stream analysis tool was carried out. Based on the VSM analysis, it was found the value added activities of 71% of the total production time and 29% of other activity times (non value added). In the case study occurred the waste for the operator's work method at the station of printing and cutting station. The VSM was performed to reducing the waste. The result depicted reduction in lead time on the production floor was 2.3 hours. So, the company in the case study can eliminate the waste time in their production process activities.